A shell-less hen's egg test as infection model to determine the biocompatibility and antimicrobial efficacy of drugs and drug formulations against Pseudomonas aeruginosa - Warncke, Paul; Fink, Sarah; Wiegand, Cornelia; Hipler, Uta-Christina; Fischer, Dagmar (International Journal of Pharmaceutics, 2020)
A shell-less hen's egg based infection test with Pseudomonas aeruginosa was established to investigate the antimicrobial efficacy of drugs and drug formulations close to the in vivo situation. The test system using preincubated fertilized chicken eggs transferred in petri dishes was optimized with respect to the controlled local application of liquid materials and bacteria as well as the bacterial cultivation conditions. The applicability of the ex ovo infection model was confirmed with antimicrobial susceptibility tests using tobramycin, ciprofloxacin and meropenem. The validity of the ex ovo data was demonstrated by correlation with in vitro data of the CellTiter®-Blue and the microplate laser nephelometry assay. Real-time imaging of the progress of infection and the efficacy of the treatment could be realized by the MolecuLight i:X™ technique. Furthermore, in a proof-of-concept efficacy, biocompatibility and even the presence of irritants were determined side-by-side using commercial ophthalmics. In conclusion, this egg based infection model could bridge the gap between in vitro and in vivo models for the evaluation of antimicrobial susceptibility to reduce animal tests according to the 3R concept.
CRIS-Team Scopus Importer:2020-10-13
Keywords: Antibiotics; Antimicrobial; Cytotoxicity; Eye drops; Hen's egg; Pseudomonas aeruginosa